War on Terror - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc